Open-label pilot study of interferon gamma-1b in Friedreich ataxia - Seyer, L.; Greeley, N.; Foerster, D.; Strawser, C.; Gelbard, S.; Dong, Y.; Schadt, K.; Cotticelli, M. G.; Brocht, A.; Farmer, J.; Wilson, R. B.; Lynch, D. R. (Acta neurologica Scandinavica, 2015)
Objectives/Aims This is an open‐label trial of the safety of interferon gamma‐1b (IFN‐γ) and its effect on frataxin levels and neurologic measures in 12 children with Friedreich ataxia. Materials and Methods Interferon gamma‐1b was administered via subcutaneous injection three times weekly. The dose increased from 10 to 50 mcg/m2 during the first four weeks and then remained at 50 mcg/m2 for final eight weeks. Safety assessments included laboratory testing, electrocardiogram, and monitoring of adverse events. The primary efficacy outcome measure was frataxin level in whole blood. Secondary measures included frataxin levels in multiple tissues, frataxin mRNA levels, Friedreich Ataxia Rating Scale (FARS) scores and other neurologic evaluations. Statistical analyses were performed via SAS and STATA. Results Interferon gamma‐1b was well tolerated with no serious adverse events, and only two subjects reporting severe adverse events and subsequent dose reductions. Small but significant changes in frataxin levels were observed in red blood cells, PBMC, and platelets after 12 weeks of treatment. However, the magnitude of change was small and varied between tissues. Mean improvement in FARS score was equivalent to roughly 18 months of disease progression after 12 weeks of treatment (P = 0.008). No other statistically significant changes were observed. No statistically significant relationships were observed between frataxin protein levels, FARS scores, and in vivo IFN‐γ levels. Conclusions Interferon gamma‐1b improved FARS scores without a clear relationship to changes in frataxin levels. Larger, longer placebo‐controlled trials including biochemical assessments in affected tissues are necessary to evaluate fully the efficacy and utility of IFN‐γ in FRDA.